Digital branding kedung ayu sebagai destinasi wisata keluarga berbasis kearifan lokal - roosinda, fitria widiyani; Ayu P, Delmarrich Bilga; Ekantoro, Julyanto (Jurnal Komunikasi Profesional, 2021)
Family travel destinations developed after the Covid-19 pandemic. Kedung Ayu is one of the tourist destinations with local wisdom in Ledug Village, Prigen District, Pasuruan Regency. The village of Ledug, where most of the residents are farming ornamental flowers, only rely on income from selling ornamental flowers, even though in that village there are other potentials that can be developed, one of which is a river with three waterfalls. Previously, this river had been filled with plastic waste for decades and various wastes, both dry and liquid. Its smells not good, plus many dry waste, also anonymous. The Abdimas program which aim developed digital branding with four programs has made the river a new family tourist destination named Kedung Ayu. The four programs are the socialization of family tourism, optimization of river cleaning, making Instagrammable photo spots and social media branding. The four programs are expected to empower villagers by increasing the number of visits through promotions both online and offline.Keywords: Â Digital Branding; Kedung Ayu; Family Travel Destination; Local Wisdom.